Die Benennung und Bestimmung der Räume im südlichen Repräsentativteil des Geschosses des zweiten „Hochmeisterpalastes“ auf der Marienburg im Mittelalter im Lichte der Schriftquellen - Jóźwiak, Sławomir; Trupinda, Janusz (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2021)
Nomenclature and intended use of the rooms of the southern (representative) part of the upper floor of the “palace” of Grand Masters in the Marienburg Castle in the Middle Ages on the basis of written sources The analyses carried out in this article concerning the southern part of the upper floor of the new (second) “palace” of the Teutonic Order’s superiors in the late Middle Ages allow to formulate several important conclusions. First of all, the building certainly existed before 11 September 1392, but it cannot be ruled out that it was erected at the beginning of the 1370s. In the fifteenth-century sources, its entire southern representative part (looking from the so-called Low and High Halls) along with five rooms of different sizes located there, were referred to as the “Summer (or, less often, Winter) chamber (gemach)”. This name comes from the most characteristic interiors located there: the “Summer Refectory” / “Great Summer Hall” in the western part and the Winter Refectory in the central part. The thorough analysis of medieval written sources carried out in this article allows for the formulation of the thesis that the chamber located in the easternmost part of the southern part of the “palace”, supported by two columns, should be identified as the “Minor Summer Hall” (aula minor estivalis), which was recorded in the transumpt of 14 May 1456. Thus, all the suggestions concerning this interior and its supposed intended use in the discussed period, hitherto put forward by the researchers who have so far formulated their conclusions in isolation from the written accounts of the period, should be rejected.